Extraction and Partial Purification of Protease from Fermented Beans Using Aspergillus niger - Timothy, Mgbede; Emochone, Roy Yohanna; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
Proteases are enzymes that are found everywhere and play important roles in both the creation and breakdown of substances in living organisms. The utilization of microbial proteases in food fermentation is a long-standing practice that has now expanded to various industries due to advancements in the 'omics' era and genetic and protein engineering techniques. The protease enzyme was derived from Aspergillus niger, which was isolated from fermented cooked discarded beans. The enzyme was partially purified and described utilizing an affordable and environmentally friendly modified technique. The impact of temperature, pH, and manufacturing time on the enzyme was assessed. The optimal conditions for protease generation were a temperature of 40°C, a pH of 7.0, and duration of 6 days. The kinetic parameter values for Km and Vmax were determined to be 0.9181 mg/mL and 1.08914 µmol/min respectively. The protein determination experiment showed that the highest protein production occurred on day 6, following 5 days of optimal protein production. The research has shown that Aspergillus niger can efficiently generate protease at a low cost, making it suitable for various industrial applications including pharmaceuticals, food production, detergents, and cosmetics.